Legal culture as a factor of social stability - M M Akulich; V V Pit’ (Vestnik Rossijskogo universiteta družby narodov. Seriâ Sociologiâ, 2015)
The article examines legal culture as a factor of stability in developing societies referring to the concepts of culture proposed by P.A. Sorokin, L.N. Kogan, M.T. Iovchuk and other famous sociologists. The authors state that in the modern sociological literature legal culture is studied mainly from the theoretical rather than empirical standpoint: the sociology has accumulated a lot of data on the legal culture, although its study in the context of agreements and conflicts, stability and destructiveness is not enough. Legal culture should be regarded as a regulator and stabilizer of social interactions and relationships in both specific countries and the global space. Thus, identifying regional and global aspects of legal culture has become an important theoretical problem of the sociological studies nowadays as well as considering legal culture in relation to moral, economic and political values and priorities. The authors argue that it is not possible to build a state of law and civil society without raising the level of legal culture, and present the results of the sociological study of the legal culture in the south of the Tyumen region conducted in 2013. This survey revealed an average level of following the law in 55% of the local population, although 90% consider themselves law-abiding citizens. At the same time, 46% believe in the possibility to manipulate the law, and 60% approve the principle of equity of the law. The authors conclude that the identified average level of legal culture among the local population is an indicator of a quite stable and successful development of the region under study.